Monitoring system for transformer - Ahmad, Nasarudin; Wahid, Herman; Sahlan, Shafisshuaza; Md. Yunos, Yusri; Abas, Khairul Hamimah (Penerbit UTHM, 2016)
The cost of a power transformer which can cost up from $2million to $4 million [1], is one of the factors that motivate electrical company to take care of its power transformer in order to run smoothly throughout its recommended life span. Currently, transformer around the world had reached an old age which is an average age of 30 years for industry plant and 40 years for utility use [1]. According to an international survey, failure rate is increasing proportionally with age [2]. Besides, any failure to a transformer can cost up to $15 million [1] which include buying a new transformer, environmental clean-up, add on modifications of site work and so forth. Moreover, substation where power transformer is located is usually unstaffed. As a result, performance of power transformer cannot be identified by the maintenance crew or person in charge of the company. Hence, typically, maintenance crew may take action by checking the power transformer on-site after a certain interval. Besides, maintenance of power transformer will be carry on with a simple time-based maintenance (TBM), which repairs all the available transformers after specified interval. Due to financial constraint, TBM method can no more be applied, because TBM cause a lot of unnecessary repair and waste a lot of unnecessary cost. As a result, maintenance crew starts focusing on conditional-based maintenance (CBM), which gives more focuses on critical transformer. Hence, maintenance will be according to the health condition of the power transformer [1]. With the aid of a remotely monitoring system for power transformer, maintenance crew able to monitor the status of critical transformer much convenient. Therefore, instead of doing petrol to check on unstaffed substation, maintenance crew can monitor the performance of power transformer remotely.